POLA ASUH IBU JANDA DALAM MENANAMKAN NILAI-NILAI PENDIDIKAN KARAKTER ANAK STUDI KASUS DESA EMBACANG KABUPATEN OGAN ILIR - MESI SULASTRI; ARDI SAPUTRA; AZIZAH HUSIN; HENNY HELMI (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the parenting patterns of single mothers in instilling character education values in children in Embacang Village, Ogan Ilir Regency. The background of this research is the increasing number of single-parent families, particularly single mothers who bear dual roles as caregivers and breadwinners, which may influence the process of character development in children. This study employs a qualitative descriptive approach. Data were collected through in-depth interviews, observations, and documentation involving single mothers and their children as research subjects. The results of the study indicate that single mothers apply various parenting styles, including authoritarian, democratic, and permissive approaches. These parenting patterns are implemented through several methods such as giving advice, establishing rules, providing supervision, habituation, and exemplifying good behavior. The character values instilled in children include honesty, respect, responsibility, fairness, caring, cooperation, and moral courage. Among these, the democratic parenting style tends to be more effective in fostering independence, responsibility, and self-confidence in children. In conclusion, parenting patterns of single mothers play a crucial role in shaping children’s character. Despite facing various challenges, single mothers are able to instill positive character values effectively through appropriate parenting strategies. Therefore, strengthening parenting skills is essential to support optimal character development in children within single-parent families.